2019
DOI: 10.1108/bfj-06-2018-0400
|View full text |Cite
|
Sign up to set email alerts
|

Does social media usage affect online purchasing intention for wine? The moderating role of subjective and objective knowledge

Abstract: Purpose The purpose of this paper is to investigate the influence that social media usage has on the online purchases of wine and to examine whether objective and subjective knowledge moderates this relationship. Design/methodology/approach A structured questionnaire was completed by a sample of 2,597 Italian wine consumers. A multinomial logistic model was used to assess how the investigated variables influenced online purchasing behavior. Findings Social media usage was found to be positively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 51 publications
3
41
0
9
Order By: Relevance
“…Variable measurement is a measuring tool used to quantify the information provided by consumers if they are required to answer questions that have been formulated in a questionnaire (Noor, 2011). The measurement scale that researchers used in this study was the Likert scale.…”
Section: Measurement and Data Collectionmentioning
confidence: 99%
“…Variable measurement is a measuring tool used to quantify the information provided by consumers if they are required to answer questions that have been formulated in a questionnaire (Noor, 2011). The measurement scale that researchers used in this study was the Likert scale.…”
Section: Measurement and Data Collectionmentioning
confidence: 99%
“…Kotler, 2000), (Rollo, 2004), (Schögel, M. and Sauer, 2002), (Kelly, 2004), (Rollo, 2004) (Schögel, M. and Sauer, 2002), (Easingwood, C. and Storey, 1996)(Ph. Kotler, 2000) (Schögel, M. and Sauer, 2002), (Pucci et al, 2019).…”
Section: Multi Channel Marketingmentioning
confidence: 99%
“…Pemanfaatan toko online dan offline dapat mempengaruhi minat pembelian pada konsumen (Verhagen & van Dolen, 2009). Hal serupa juga di ungkapkan pada penelitian (Pucci et al, 2019) yang menyatakan penggunaan beragam media online (social media) menunjukkan peranan penting dalam proses pembelian, serta peggunaan media yang efektif akan dapat membantu peningkatan penjualan.…”
Section: Pembahasan 1 Pengaruh Multi-channels / Multi Platform Terhadap Minat Beliunclassified
See 1 more Smart Citation
“…Despite the significant impact of SM on wine customers and winery businesses [9,10] digital marketing for wine is still complex [11]. Wineries are increasingly adopting SM [12] but at a slow pace, as most lack the knowledge to incorporate and exploit SM effectively in their marketing strategy [13][14][15][16]. A study of Italian wineries has shown that it is principally large wineries with a number of employees with SM knowledge and skills that are highly motivated for adopting SM [17].…”
Section: Introductionmentioning
confidence: 99%